Download presentation

1
**Solving Quadratic Equations Section 1.3**

2
**What is a Quadratic Equation?**

A quadratic equation in x is an equation that can be written in the standard form: ax² + bx + c = 0 Where a,b,and c are real numbers and a ≠ 0.

3
**Solving a Quadratic Equation by Factoring.**

The factoring method applies the zero product property: Words: If a product is zero, then at least one of its factors has to be zero. Math: If (B)(C)=0, then B=0 or C=0 or both.

4
**Recap of steps for how to solve by Factoring**

Set equal to 0 Factor Set each factor equal to 0 (keep the squared term positive) Solve each equation (be careful when determining solutions, some may be imaginary numbers)

5
**Example 1 Solve x² - 12x + 35 = 0 by factoring.**

Set each factor equal to zero by the zero product property. Solve each equation to find solutions. The solution set is: (x – 7)(x - 5) = 0 (x – 7)=0 (x – 5)=0 x = 7 or x = 5 { 5, 7 }

6
**Example 2 Solve 3t² + 10t + 6 = -2 by factoring.**

Check equation to make sure it is in standard form before solving. Is it? It is not, so set equation equal to zero first: 3t² + 10t + 8 = 0 Now factor and solve. (3t + 4)(t + 2) = 0 3t + 4 = t +2 = 0 t = t = -2

7
Solve by factoring.

8
**Solve by the Square Root Method.**

If the quadratic has the form ax² + c = 0, where a ≠ 0, then we could use the square root method to solve. Words: If an expression squared is equal to a constant, then that expression is equal to the positive or negative square root of the constant. Math: If x² = c, then x = ±c. Note: The variable squared must be isolated first (coefficient equal to 1).

9
**Example 1: Solve by the Square Root Method:**

= x = ± 4

10
**Example 2: Solve by the Square Root Method.**

x = ±i

11
**Example 3: Solve by the Square Root Method.**

x – 3 = 5 or x – 3 = -5 x = x = -2

12
**Solve by the Square Root Method**

13
**Solve by Completing the Square.**

Words Express the quadratic equation in the following form. Divide b by2 and square the result, then add the square to both sides. Write the left side of the equation as a perfect square. Solve by using the square root method. Math x² + bx = c x² + bx + ( )² = c + ( )² (x )² = c + ( )²

14
**Example 1: Solve by Completing the Square.**

x² + 8x – 3 = 0 x² + 8x = 3 x² + 8x + (4)² = 3 + (4)² x² + 8x + 16 = (x + 4)² = 19 x + 4 = ± x = -4 ± Add three to both sides. Add ( )² which is (4)² to both sides. Write the left side as a perfect square and simplify the right side. Apply the square root method to solve. Subtract 4 from both sides to get your two solutions.

15
**Example 2: Solve by Completing the Square when the Leading Coefficient is not equal to 1.**

2x² - 4x + 3 = 0 x² - 2x = 0 x² - 2x + ___ = ____ x² - 2x + 1 = (x – 1)² = x – 1 = ± x = 1 ± Divide by the leading coefficient. Continue to solve using the completing the square method. Simplify radical.

16
Quadratic Formula If a quadratic can’t be factored, you must use the quadratic formula. If ax² + bx + c = 0, then the solution is:

17
a = 1 b = -4 c = -1 Solve

18
Solve

19
Solve

20
Discriminant The term inside the radical b² - 4ac is called the discriminant. The discriminant gives important information about the corresponding solutions or answers of ax² + bx + c = 0, where a,b, and c are real numbers. b² - 4ac Solutions b² - 4ac > 0 b² - 4ac = 0 b² - 4ac < 0

21
**Tell what kind of solution to expect**

Similar presentations

© 2024 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google